Volatility Index as a Timing Tool in S&P 500 with Style Rotation - Palotie, Nico (My University, 2020)
The strong negative correlation between contemporaneous changes of VIX and stock returns is well-documented by multiple studies such as Fleming, Ostdiek and Whaley (1995), Giot (2005) and Rubbaniy, Asmerom, Abbas and Naqvi (2014). Due to the highly negative relationship between VIX and stock returns, timing possibilities with VIX in the equity markets are an increasingly examined topic in economic science. Giot and Banerjee, Doran and Peterson (2007) find that future stock returns are always positive (negative) for very high (low) levels of VIX regardless of the holding period length. This thesis contributes to these previous studies by investigating VIX as a potential timing tool when investing in equity markets and whether style rotation has an additional effect on the returns of a VIX timing strategy. This thesis examines data from 29th January 1993 to 31st December 2018 and investigates how positions selected in S&P 500, Fama-French 5 factors (Fama and French 2015) and momentum factor perform on different levels of VIX with different holding periods. The key method in this thesis is a 500-day rolling ranking method inspired by Giot (2005) to create relative ranks for different levels of VIX. The factor return results are used to construct long-short portfolios for each factor to examine if VIX timing strategies with style rotation produce excess returns compared to conventional factor portfolios. The results show that the highest VIX levels are excellent indicators for positive future returns in S&P 500. However, the findings of this study do not support the results of Giot (2005) and Banerjee, Doran and Peterson (2007) that low levels of VIX always lead to negative stock returns. In addition, this thesis reveals that the Fama-French 5 and momentum factors exhibit different future returns depending on the level of VIX and that the size and operating profitability factors can be used by investors in profitable style rotation strategies combined with VIX timing.
Keywords: VIX, market timing, Fama-French 5 factors, negative correlation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance